2012
DOI: 10.1186/1471-2105-13-s13-s7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of markers associated with global changes in DNA methylation regulation in cancers

Abstract: DNA methylation exhibits different patterns in different cancers. DNA methylation rates at different genomic loci appear to be highly correlated in some samples but not in others. We call such phenomena conditional concordant relationships (CCRs). In this study, we explored DNA methylation patterns in 12 common cancers using data of 2434 patient samples collected by The Cancer Genome Atlas project. We developed an exploratory method to characterize CCRs in the methylation data and identified the 200 gene marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…For example, Figure 6 shows that the methylation of SOX8 is significantly associated to low SOX8 expression in breast cancer and kidney renal clear cell carcinoma but not in the other three cancer types. Such tissue-specific relationship echoes a previous result that hierarchical clustering of methylation data is able to separate tissue types and cancer subtypes [14,15]. Four genes showed significant methylation-expression association in all five individual cancer types, BST2, SLA2, GSTT1, and GSTM1.…”
Section: Resultssupporting
confidence: 83%
“…For example, Figure 6 shows that the methylation of SOX8 is significantly associated to low SOX8 expression in breast cancer and kidney renal clear cell carcinoma but not in the other three cancer types. Such tissue-specific relationship echoes a previous result that hierarchical clustering of methylation data is able to separate tissue types and cancer subtypes [14,15]. Four genes showed significant methylation-expression association in all five individual cancer types, BST2, SLA2, GSTT1, and GSTM1.…”
Section: Resultssupporting
confidence: 83%
“…In DNA methylation, it has been shown that the correlation of methylation rates between two CpG sites is related to the distance (see Figure S4 ), and the clustering effect can be as high as 0.7 for probes within 200 bp [ 53 ]. To address whether the mRNA m 5 C methylation also exhibits a clustering effect, we examined the proportion of m 5 C sites that are within 10 bp distance of other m 5 C sites and compared this proportion with that from 1000 times of random permutation.…”
Section: Resultsmentioning
confidence: 99%
“…The samples are composed of cell lines and 12 cancer types. We selected 200 CpG sites using conditional correlation [13], and used the methylation data of those CpG sites to build a minimum-spanning tree. The tree describes the similarities among the samples according to their methylation status of the selected CpG sites.…”
Section: Resultsmentioning
confidence: 99%